2019
DOI: 10.1002/ese3.301
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of clay minerals and its effect on coal permeability and gas production: A case study of southern Qinshui Basin, China

Abstract: The permeability damage of high‐rank coal reservoirs is the main factor affecting the development of coalbed methane (CBM) in the late production stage. Coal core samples from southern Qinshui Basin were saturated with actual formation water, 1/2 salinity formation water, and distilled water to study the swelling of clay minerals. Then, the mechanism of permeability change caused by water sensitivity and its effect on gas production was discussed. The results show that the permeability decrease caused by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Because research on the SS of coal is scarce, further discussions are limited. Zhao, 53 Hu et al, 54 Tao et al, 10 Gong, 52 Zuo et al, 55 Tian and Wu 56 applied anthracite samples to study WS; Wang et al 21 applied lignite samples to study WS; and Gao et al, 57 Geng et al 58 and we applied bituminous coal samples to study WS. Table 5 displays the results of these studies.…”
Section: Migration Potential and Migration Pathway Of Minerals During...mentioning
confidence: 99%
See 1 more Smart Citation
“…Because research on the SS of coal is scarce, further discussions are limited. Zhao, 53 Hu et al, 54 Tao et al, 10 Gong, 52 Zuo et al, 55 Tian and Wu 56 applied anthracite samples to study WS; Wang et al 21 applied lignite samples to study WS; and Gao et al, 57 Geng et al 58 and we applied bituminous coal samples to study WS. Table 5 displays the results of these studies.…”
Section: Migration Potential and Migration Pathway Of Minerals During...mentioning
confidence: 99%
“…It can be seen that WS permeability damage ratios vary tremendously even for coals with the same ranks. For instance, Tao et al 10 reported WS permeability damage ratios of anthracite, which vary from 5.21 to 52.08%, and all data of anthracite from Zhao, 53 Hu et al, 54 Tao et al, 10 Gong, 52 Zuo et al, 55 and Tian and Wu 56 show that WS permeability damage ratios of anthracite vary from 5.21 to 83.06%, indicating that there is no close relationship between the WS damage degree and coal rank.…”
Section: Migration Potential and Migration Pathway Of Minerals During...mentioning
confidence: 99%
“…20,27,[43][44][45][46][47] Among them, the influence of in situ stress regime on K occurs throughout the whole process of CBM exploration and development. 20,27,[43][44][45][46][47] Among them, the influence of in situ stress regime on K occurs throughout the whole process of CBM exploration and development.…”
Section: In Situ Stress Influence On Coal Permeabilitymentioning
confidence: 99%
“…As one of the most important factors in the determination of CBM productivity, K has been influenced by complex geological factors, for example, structural framework, in situ stress regime, burial depth, coal structure, and development of natural fractures. 20,27,[43][44][45][46][47] Among them, the influence of in situ stress regime on K occurs throughout the whole process of CBM exploration and development. In other words, the pore-fracture system varies with the change of in situ stress regime, along with K of coal reservoirs.…”
Section: In Situ Stress Influence On Coal Permeabilitymentioning
confidence: 99%
“…On the other hand, Hanson et al (1999) found that fine grained soils may be affected by reduced permeability by sodium (Na + ) induced clay swelling with consequent disruption of soil's aggregates, so attention must be paid to the Comp salinity and Na + content. In fact, clay swelling may cause a reduction of soil permeability, because clay minerals once dispersed from soil's aggregates may fill soil pores and reduce water flow (Tao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%